Significant increases of the amygdala between immediate and late postpartum: Pronounced effects within the superficial subregion. Issue 9 (8th June 2021) - Luders, Eileen; Gaser, Christian; Gingnell, Malin; Engman, Jonas; Sundström Poromaa, Inger; Kurth, Florian
Abstract: Research exploring the underlying neuroanatomical correlates of early motherhood seems to suggest that the period after giving birth is marked by tissue increases in the mother's brain. While some studies point to the amygdala as one of the areas undergoing postpartum changes, existing analyses did not discriminate between the different subregions of this functionally heterogeneous structure. Thus, to further extend this understudied field of research and to better understand the potential role of the amygdala when transitioning to motherhood, we applied an advanced region‐of‐interest technique that enabled us to analyze the amygdala as a whole as well as its different subareas, specifically the left and right centromedian (CM), laterobasal (LB), and superficial (SF) regions. Comparing the brains of 14 healthy women between immediate postpartum (within 1–2 days of childbirth) and late postpartum (at 4–6 weeks after childbirth), we revealed increases of the amygdala. However, effects manifested differentially across subareas, with particularly strong effects for the SF region, moderate effects for the CM region, and no effects for the LB region. These findings might reflect region‐specific adaptations of the mother's brain tuning into the distinct and ever‐changing needs of a newborn, either as a cause for it or as a consequence thereof. Abstract : Our longitudinal study revealed increases of the amygdala during the postpartum period. Volumes and subvolumes of the amygdala were analyzed by integrating imaging‐based signal intensities with cytoarchitectonically defined probabilities. ​